60.7k views
1 vote
HELP MEEE!!!! PLZZZZZZZ

HELP MEEE!!!! PLZZZZZZZ-example-1

2 Answers

5 votes

Answer:

-24

Explanation:

So first you take f(x) and replace 1 in x so its 1-5 which is -4 you then replace that in g(x) which would be 6*-4 which is 24. Also this isn't college math going this in first year of high school. Imao

User Daydreaming Duck
by
4.6k points
6 votes

Answer:

The answer is 24.

Explanation:

6x(x²-5(1))

6x³=30x

x²÷x=30-60

x=30-6

x= -24

User Saurabh Parmar
by
5.7k points